Reproductive Biopolitics, Demographic Anxieties, and Access to Safe Abortion: National Security and Pronatalism in the ‘Family Protection and Youthful Population’ Law in Iran - Ladan Rahbari (Social Sciences)
This paper examines the historical relationship between Shi’i jurisprudence and the Islamic Republic of Iran’s reproductive biopolitics. Using archival methods, the paper looks into the similarities and differences between religious interpretations and Iranian law. It then analyzes the implications of the recent ‘Family Protection and Youthful Population’ law, enacted in 2021 in response to fears of a looming ‘population crisis,’ and how it further restricts women’s access to abortion (care). The paper argues that reproductive policies are influenced not only by religious authorities and pronatalist patriarchal rationales but also by specific anxieties about a population crisis and decline considered a threat to the country’s national security. Reproductive policies exist within a moral framework at the intersection of demographic anxieties, biopolitics, and religious discourses that push women toward unpaid maternal labor and traditional gender roles.